Basigin expression as a prognostic indicator in stage I pulmonary adenocarcinoma. Issue 4 (12th February 2018) - Matsumoto, Toshihide; Nagashio, Ryo; Ryuge, Shinichiro; Igawa, Satoshi; Kobayashi, Makoto; Fukuda, Eriko; Goshima, Naoki; Ichinoe, Masaaki; Jiang, Shi‐Xu; Satoh, Yukitoshi; Masuda, Noriyuki; Murakumo, Yoshiki; et al.
Abstract : We established the KU‐Lu‐8 monoclonal antibody (MoAb) using a lung cancer cell line as an antigen and a random immunization method. The KU‐Lu‐8 MoAb recognizes basigin (BSG), which is a transmembrane‐type glycoprotein that is strongly expressed on the cell membranes of lung cancer cells. This study aimed to clarify the relationships between BSG expression and clinicopathological parameters and determine the prognostic significance of BSG expression in pulmonary adenocarcinoma (AC) patients. To evaluate the significance of BSG expression in lung cancer, we immunohistochemically analyzed 113 surgically resected pulmonary adenocarcinomas, and the associations between BSG expression and various clinicopathological parameters were evaluated. Kaplan‐Meier survival analysis and Cox proportional hazards models were used to investigate the effects of BSG expression on survival. Clinicopathologically, BSG expression was significantly associated with tumor differentiation, vascular invasion, lymphatic invasion, and a poor prognosis. In particular, BSG expression was significantly correlated with poorer survival in patients with stage I AC. The high BSG expression group (compared with the low BSG expression group) exhibited adjusted hazard ratios for mortality of 4.694. BSG expression is indicative of a poor prognosis in AC patients, particularly in those with stage I disease.